Integrative Holistic Early Childhood Development Program - Selian, Nurhaida (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
ABSTRACT. This research is motivated by the rapid growth of Early Childhood Education (PAUD) in Bengkalis Regency, which has not yet been developed into quality PAUD. Therefore, the government has established quality indicators for PAUD, namely the Holistic Integrative Early Childhood Development Program (PAUD HI). In this case, the Holistic Integrative Early Childhood Development Program (PAUD HI) is a program initiated by the government through the Ministry of Education under the Directorate General of Early Childhood Education. This program is implemented to assess the quality of PAUD in Bengkalis Regency, specifically focusing on TK Negeri Pembina in Bengkalis Regency.This study employs a qualitative descriptive approach with data collection techniques such as observation, interviews, and documentation. The results of this research indicate that TK Negeri Pembina has developed the completeness of PAUD HI in Bengkalis Regency. The factors influencing the development of the PAUD HI Program at TK Negeri Pembina in Bengkalis Regency into a quality PAUD are categorized into two: internal and external factors.Internal factors affecting the development of PAUD HI include misconceptions about PAUD HI in many TK Negeri Pembina schools in Bengkalis Regency, especially among educators who have not provided the essential needs of children comprehensively. The competencies of educators are not fully integrated with PAUD HI, and parents' awareness of the impact of violence on children is still low. External factors include TK Negeri Pembina not having standardized essential needs fulfilled by the Bengkalis Regency Government to become a quality PAUD.KeyWord. Holistic Integratif Development